Political Participation of Persons with Disabilities in Election: The Case of Regional Elections in Bantul, Indonesia - Yaniar, Syifa Annisa; Simamora, Naufal Bariq Alauddin; Hanifah, Hana Tiara; Wijayani, Sabrina (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This article analyzes the involvement of disability groups in the regional election and how this will contribute to the upcoming 2024 General Election in Indonesia. Groups of people with disabilities often face discrimination, which hinders the realization of their rights as outlined in Law Number 8 of 2016 regarding Persons with Disabilities. Ensuring such rights are fulfilled is crucial for social progress and the welfare of individuals, particularly in democratic nations. The approach in this study uses the theory of political participation and the concept of human rights as a theoretical framework. Meanwhile, the research method is qualitative, with descriptive analysis to discuss the intended topic. The collection of research data was obtained from interviews and literature studies. This article examines the case study of the involvement of persons with disabilities in the 2020 Bantul Regional Election and its influence on the 2024 General Election. Bantul is a district in the Special Region of Yogyakarta Province in that it has the largest population with disabilities. As a result, special attention is needed to ensure that the political rights of the disabled group in Bantul are guaranteed. The findings show several forms of involvement of disability groups in the previous elections in 2019 and 2020. The deficiencies in these elections should be addressed to improve access for disability groups making democracy inclusive. This article, then, contributes to the studies of the political participation of persons with disabilities in democracy in the context of regional elections.